Advances and Future Prospects of Pigment Deposition in Pigmented Rice - Hong Lang; Xingtian Jia; Bing He; Xiaoming Yu (Plants)
Pigmented rice, particularly the black and red varieties, is popular due to its better nutritional value. Anthocyanins and proanthocyanidins are two major flavonoid subcategories with broad physiological functions and therapeutic significance. However, pigment deposition is a complex process, and the molecular mechanism involved remains unknown. This review explores the metabolites responsible for the pigmentation in various rice tissues. Moreover, the current challenges, feasible strategies, and potential future directions in pigmented rice research are reported.